Tele-guidance for intensive physiotherapy in older patients with type 2 diabetes: a study protocol for randomized controlled trial - Hiroaki Kataoka; Takuo Nomura; Toshihiro Kawae; Hiroyuki Oka; Yukio Ikeda (Japanese Society of Physical Fitness and Sports Medicine, 2020)
A recent trend in Japan is the increasing number of older patients with diabetes. Treatment for diabetes mellitus in older patients involves a wide variety of strategies, not only for better glycemic control, but also for the prevention and improvement of locomotive syndrome, sarcopenia, and frailty. Previous studies have shown that tele-guidance treatment interventions are effective for weight loss and increase in physical activity, but their effects on locomotive syndrome, sarcopenia, and glycemic control have not been examined. The objective of this study is to assess the efficacy of tele-guidance for intensive therapeutic interventions for diabetes mellitus in older patients, carried out by a qualified physical therapist with diabetes-specific qualifications and knowledge. This multi-center study, including 6 hospitals in Japan, is a prospective, parallel-group, single-blinded, randomized controlled trial. A total of 78 patients will be registered based on our preliminary studies. Patients aged 65-89 years with type 2 diabetes mellitus will be assigned randomly to intensive intervention and control groups. The effectiveness of 6 months of intervention will be verified by a physical therapist. The primary outcome measure will be the change in isometric knee extension force (KEF), whereas the secondary outcomes will be changes in skeletal muscle mass, motor function, glycemic control, and satisfaction with the treatment. When prescribing exercise therapy to older patients with diabetes mellitus, the various risks associated with exercise should be taken into consideration. Therefore, this study has been designed to establish the efficacy of intensive physiotherapy programs in older patients with diabetes mellitus. Provided that this study shows the effectiveness of tele-guidance in improving physical function and glycemic control, it can be a new intervention strategy for exercise therapy in older diabetes patients.